Streaming instability of a dusty plasma in the presence of mass and charge variation - Pandey, B.P.; Dwivedi, C.B. (My University, 1995)
We study the effect of the mass and charge dynamics on the collective behaviour of a dusty plasma. It is shown that the finite non-zero streaming velocity of the dust grains leads to a novel coupling of the dust mass fluctuation with other dynamic variables of the plasma and the grains. The mass fluctuations causes a collisionless dissipation and provides an alternate channel for the beam mode instability to occur. Physically the negative energy wave associated with the beam mode couples to the mass fluctuation induced dissipative medium to produce the instability. We conclude that the higher value of the ion mass density to the dust mass density ratio reduces the threshold value for the onset of the instability. Its application in the astrophysical context is discussed.
Keywords: Dusty plasma; Charge fluctuation; Mass fluctuation